Effect of Permittivity of Plasma Medium on the Particle Properties and Electric Field in a Magnetized Plasma Sheath - Dahal, Prem; Chalise, Roshan; Khanal, Raju (Amrit Research Journal, 2022)
The plasma sheath, a thin layer having sharp gradients, is necessary to be formed at any material wall in exposure with plasma for its stability. Characteristics of magnetized plasma sheath formed in front of a material wall for different permittivity of plasma medium has been studies using the kinetic trajectory simulation (KTS) model. The electron density, ion density, electric field and potential decreases on moving away from the sheath entrance but total charge density increases. As plasma is composed of charged particles, any variation in the permittivity of the medium has significant effects on the sheath properties. It is found that on increasing the permittivity of the medium, the electric potential strength and hence electric field decreases because of increased shielding ability of the plasma. The results are in qualitative agreement with earlier studies based on the fluid approach but the kinetic approach is more accurate quantitatively providing a better perception of plasma-wall transition phenomena.